REPROGRAMAÇÃO DOS FLUIDOS DE PERFURAÇÃO EM POÇOS DA SABESP NO VALE DO PARAÍBA - Bianchi Neto, César Bianchi; Franco Filho, Fernando Wili Bastos; Souza, João Carlos Simanke de (Águas Subterrâneas, 1997)
Resumo não disponível.